1981
DOI: 10.1083/jcb.90.3.743
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane linkage between surface glycoproteins and components of the cytoplasm in neutrophil leukocytes.

Abstract: An experimental approach is described that enables the analysis of interactions between exogenous surface ligands and components of the cytoplasm in neutrophil leukocytes . Neutrophils treated with the nonionic detergent Lubrol FIX, under controlled conditions, yield intact detergent-insoluble ghosts . Morphological analysis of neutrophil ghosts shows that they retain the original dimensions of the cell and consist almost entirely of a peripheral filamentous network, representing the submembranous cortical web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 36 publications
(43 reference statements)
0
35
0
Order By: Relevance
“…Concomitant with actin polymerization, the ligandreceptor complex is converted from a fast dissociating (or low affinity) form to a slow dissociating (or high affinity) form (10, 1 1). Several labs have also demonstrated that following ligand binding, the Con A, Fc, FMLP, CR1, and CR3 (C3bi/MO-1) receptors are recruited to the detergent insoluble actin-containing cytoskeleton of PMNs (3,4,(12)(13)(14). The specific association of these receptors with actin filaments is further supported by the fact that cytochalasin D blocks the formation of ligand-receptor complexes (3,12,14).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Concomitant with actin polymerization, the ligandreceptor complex is converted from a fast dissociating (or low affinity) form to a slow dissociating (or high affinity) form (10, 1 1). Several labs have also demonstrated that following ligand binding, the Con A, Fc, FMLP, CR1, and CR3 (C3bi/MO-1) receptors are recruited to the detergent insoluble actin-containing cytoskeleton of PMNs (3,4,(12)(13)(14). The specific association of these receptors with actin filaments is further supported by the fact that cytochalasin D blocks the formation of ligand-receptor complexes (3,12,14).…”
Section: Introductionmentioning
confidence: 83%
“…Con A-induced activation of human platelets causes the recruitment of glycoprotein IIb/IIIa and doubles the amount of detergent insoluble actin. In pig PMNs, the recruitment of 217, 170, and 147 kD surface glycoproteins to the detergent insoluble cytoskeletal fraction parallels the capping of Con A receptors (12). In PC12 cells exposure to WGA causes occupied nerve growth factor (NGF) receptors to switch from rapid to slow dissociation kinetics (50).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the GPIIb-III membrane actin complex bound with high efficiency to rabbit f-actin in vitro in a Ca++-independent manner, whereas the monomeric forms found in the Triton-soluble fraction did not bind to actin. These results indicate that two forms of GPllb and III exist: one that binds directly to endogenous membrane actin and one that does not.Numerous studies have provided largely indirect evidence for transmembrane interactions among surface proteins and receptors of cells and an internal membrane matrix composed of actin and other cytoskeletal proteins (3,5,7,10,14,16,17,19,23,25,27,31,35,40,45). Indeed, a number of studies have shown that the surface topography and lateral mobility of receptors can be modulated by the underlying cytoskeleton and its associated contractile and motile elements (20,28,30,31,36,37,39).…”
mentioning
confidence: 99%
“…ConA is a plant lectin that binds to mannosylated glycoproteins and glycolipids on the surface of a wide range of cell populations. It represents an established tool to induce cell activation and to study cell membrane structure and dynamics such as the mobility and redistribution of membrane protein receptors (30,31,38). Response of stimulated lymphocytes was determined by means of characteristic IL-2 release.…”
mentioning
confidence: 99%